Diseño de una colección de indumentaria femenina inspirada en el grupo BTS para miembros del fandóm ARMY. - Benalcazar Caviedes, Mayra Carolina (2024)
This thesis focuses on the design of a women's collection inspired by the group BTS for the ARMY Ecuador community. This initiative stems from the identification of a lack of attention to the ARMY community in the local fashion market, where the current offer does not adequately reflect the diversity and sophistication of the group's followers. Interest in BTS has increased significantly in Ecuador, and the proposed collection seeks to meet the needs of a multifaceted segment of the population, composed mainly of young adult women. The overall objective of the thesis is to develop a clothing line that not only captures the artistic essence of BTS, but also integrates harmoniously with the daily lifestyle of its followers. To achieve this objective, an analysis of the aesthetics and symbology of BTS has been carried out in order to implement the elements in the final collection. The research is based on a qualitative and quantitative approach, through surveys and a focus group to the ARMY community in Ecuador we have obtained information about their tastes, preferences and needs, young people say that there is a great prejudice about their community which influenced the availability of garments related to the Kpop group in the market. And the design of an Army-focused collection can meet their demands. The marketing of the collection will be done through social networks in the ARMY community groups in Ecuador.